MAKNA GRAMATIKAL KATA MA DALAM KITAB ADAB AL-‘ALIM WA AL-MUTA’ALLIM KARANGAN HADROT AL-SYEKH HASYIM ASY’ARI - Nadin Arifin; Muhamad Nurhasan; Ihin Solihin (Hijai - Journal on Arabic Language and Literature, 2024)
This study is motivated by the importance of understanding the grammatical meaning of the word "ما" in Arabic. A deep comprehension of its functions is crucial for students to grasp the context of Arabic expressions. In Arabic, the word "ما" has various grammatical functions that influence the overall meaning of sentences. The monumental work Adab al-‘Alim wa al-Muta‘allim by the Indonesian scholar Hadrat al-Syekh Hasyim Asy’ari serves not only as a guide in the fields of morals and ethics but also as a resource for Arabic language learners to deepen their understanding of Arabic grammar. By analyzing the usage of the word "ما " in this book, the types of the word can be identified, highlighting the essential role of grammar in constructing text structure and meaning and conveying the author’s intended message. The purpose of this research is to identify the types of the word "ما" in *Adab al-‘Alim wa al-Muta‘allim* by Hadrat al-Syekh Hasyim Asy’ari and to understand its grammatical meanings in the text. This research is alibrary study focusing on sentences containing the word "ما ." The primary data source is *Adab al-‘Alim wa al-Muta‘allim*, limited to Chapters One through Three. Additional sources include relevant books, journals, and articles. The research approach employs semantic analysis to explore grammatical meanings. The findings reveal that the word "ما " appears 64 times in Chapters One through Three of *Adab al-‘Alim wa al-Muta‘allim*Keywords: Adab al-‘Alim wa al-Muta‘allim, Word Ma, Grammatical Meaning